Applications of differential subordination for certain subclasses of meromorphically univalent functions defined by rapid operator - Bolineni Venkateswarlu; P. Thirupathi Reddy; Settipalli Sridevi; Galla Swapna (E-Journal of Analysis and Applied Mathematics)
In this work, we investigate some applications of differential subordination for the class of meromorphic univalent functions defined by rapid operator and obtained coefficient bounds, integral representations, weighted and arithmetic mean for the class Σ(A, B, μ, θ)